India: Majoritarian Democracy from Above - Mitra, Subrata Kumar (The handbook of electoral system choice, 2004)
India belongs to a minority of post-colonial states that have made a successful transition from colonial to a stable democracy. But the path that India has taken to reach this coveted status is radically different from her western counterparts. Western democracies are the products of popular movements from below, resulting from industrial revolution, leading to the slow but inexorable rise of working men and subsequently women into political visibility, their violent struggle for participation, and finally the achievement of universal adult franchise. In contrast, there was no full-scale industrialization in India before independence. Large-scale changes in society and the economy lay in the Indian case not behind but ahead, as a beacon and a worthy goal for the nascent post-colonial state. Hence the puzzle: how could a democracy from ‘above’, based on alien values of individualism and institutions of foreign origin such as political parties and the rule of law, strike root on Indian soil, strengthening the foundations of the form of parliamentary democracy adopted at independence? Or, even more pointedly, how could the plurality rule first-past-the-post electoral system based on single-member districts survive intact in spite of the apprehensions that this particular form of vote counting creates among minorities? A detailed answer to these complex questions is beyond the remit of this chapter. Instead, it concentrates on the catalytic role of the electoral system in the transition from colonial rule to popular democracy.